Prostanglandin versus oxytocin for induction of labour in prelabour rupture of membranes. - Ong, Nabilah; Abu Ishak, Nurkhairulnisa; Raja Ismail, Raja Arif Shah; Awang, Mokhtar; Ismail, Ghazali (IIUM Press, International Islamic University Malaysia, 2017)
This study was conducted to compare the outcome in between prostaglandins and oxytocin as methods of induction of labour in prelabour rupture of membranes with unfavorable cervix. This is a prospective randomized double blinded study carried out from 1st July 2012 to 30th June 2013 at Hospital Sultan Ismail Johor Bahru. A total of 148 women with singleton pregnancies at ≥ 37 weeks, no prior uterine scar, vertex presentation, reactive cardiotocogram (CTG) were randomly assigned to receive immediate induction of labour either by intravenous oxytocin infusion or vaginal prostaglandin E2. The primary outcomes were maternal and neonatal outcome. Data was analyzed using SPSS version 10.0 and p value of <0.05 was considered to be statistically significant. 148 patients were included in this study, 73 patients in prostaglandins arm, and 75 patients in oxytocin arm. The mean age was 27.8+4.9 years old and the mean gestational age was 38.7+1.2 weeks. Majority of them (73%) presented with PROM of less than 24 hours. Following induction of labour, 68% of them achieved vaginal delivery. In the oxytocin group, induction of labour to vaginal delivery interval (7.6+4.7 versus 16.5+14.8, p<0.001) and leaking liquor to delivery interval (19.1+11.8 versus 32.3+22.4, p<0.001) were significantly shorter than the PGE2 group. However caesarean delivery was found 3 times more (32.0% versus 9.6%, p=0.001) in the oxytocin group. The rate of neonatal infections (31.5% versus 8.0%, p<0.001) and NICU admission (38.4% versus 21.3%, p=0.023) were significantly lesser in the oxytocin group. In conclusion, neither oxytocin nor PGE2 was preferred as a method of induction of labour in patients with PROM at term with unfavourable cervix. The management of term PROM therefore needs to be individualized to achieve the best maternal and neonatal outcomes. Expectant management remains as an alternative option.